Effects of anisotropy and disorder on the superconducting properties of niobium - Zarea, Mehdi; Ueki, Hikaru; Sauls, J. A. (Frontiers in Physics, 2023)
We report results for the superconducting transition temperature and anisotropic energy gap for pure niobium based on Eliashberg's equations and electron and phonon band structures computed from density functional theory. The electronic band structure is used to construct the Fermi surface and calculate the Fermi velocity at each point on the Fermi surface. The phonon bands are in excellent agreement with inelastic neutron scattering data. The corresponding phonon density of states and electron-phonon coupling define the electron-phonon spectral function, α 2 F (p, p ′ ; ω), and the corresponding electron-phonon pairing interaction, which is the basis for computing the superconducting properties. The electron-phonon spectral function is good agreement with existing tunneling spectroscopy data except for the spectral weight of the longitudinal phonon peak at ℏω LO = 23 meV. We obtain an electron-phonon coupling constant of λ = 1.057, renormalized Coulomb interaction, µ ⋆ = 0.218 and transition temperature T c = 9.33 K. The corresponding strong-coupling gap at T = 0 is modestly enhanced, ∆ 0 = 1.55 meV, compared to the weak-coupling BCS value ∆ wc 0 = 1.78 k B T c = 1.43 meV. The superconducting gap function exhibits substantial anisotropy on the Fermi surface. We analyze the distribution of gap anisotropy and compute the suppression of the superconducting transition temperature using a self-consistent T-matrix theory for quasiparticle-impurity scattering to describe niobium doped with non-magnetic impurities. We compare these results with experimental results on niobium SRF cavities doped with Nitrogen impurities.